Childhood and Youth - Schoonmaker, Sara (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course, we examine childhood, preadolescence and youth as distinct phases of social life constructed by young people and adults in the context of structural inequalities of age, race, class, gender, and sexuality. We critique the myth of childhood innocence and other prevailing norms that fail to understand young people as agents who actively engage in creating and resisting social structures and relationships. We study popular cultural texts to examine the complex ways that they communicate these norms about childhood and the relationships between children and adults. We analyze preadolescence as a time when friendships, gender relations, clique dynamics and stratification are particularly important. In the last section of the course, we examine how race, class and gender inequalities are experienced, constructed and resisted in youth and young adulthood.Course Objectives:This course is designed to empower students to:1) Understand childhood, preadolescence, and youth as phases of social life actively constructed through socialization processes, in the context of structural inequalities of age, race, class, gender and sexuality.2) Analyze popular cultural texts to critique social norms about what it means to be a child, preadolescent, and youth, highlighting the links between those norms and relations of power and inequality.3) Apply the material from the course to understand their own lives and experiences as children, preadolescents, and youth.4) Develop the willingness and ability to question assumptions about reality, society and self; and to formulate personal views of these entities in light of the material in this course. 5) Develop their critical thinking and communications skills.